Ethnoscience of Educative Values of Margondang Custom of South Tapanuli Community in Gunung Malintang Village, Barumun Tengah Subdistrict, Padang Lawas Regency - Husnul Hotima Siregar; Suranto (Jurnal Penelitian Pendidikan IPA, 2025)
This research has two objectives, first, to analyse the process of implementing margondang custom, and second, to analyse the educational values in margondang custom performed by the community in Gunung Malintang Village, Central Barumun District, Padang Lawas Regency. This research is a qualitative descriptive research. The informants in this research are the customary king (traditional leader), the village head, village officials, and the people of Gunung Malintang Village. The data collection techniques in this research are observation, interview, and documentation. Data analysis used the Miles and Huberman analysis method, which consists of data reduction, data presentation, and conclusion drawing. The research shows that the implementation of the Mandailing community margondang custom includes the stages of martahi, mangalap boru, marsattan boru, pataru itak godang, to horja godang. This procession begins with a traditional session, giving the title of king to the bridegroom, slaughtering buffalo, manortor according to customary status, patuaekkon or riding nacar, mangupa, and ends with a meal together. The margondang tradition that used to last 1-3 days is now generally only done in 1 day due to changes in people's habits. Apart from being a cultural heritage, margondang also contains educational values, namely religious, social, responsibility and moral values that are important for community life.